2001
DOI: 10.1056/nejmoa010534
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Trial of Estrogen-Replacement Therapy after Ischemic Stroke

Abstract: Estradiol does not reduce mortality orthe recurrence of stroke in postmenopausal women with cerebrovascular disease. This therapy should not be prescribed for the secondary prevention of cerebrovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
212
0
3

Year Published

2002
2002
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 807 publications
(221 citation statements)
references
References 48 publications
2
212
0
3
Order By: Relevance
“…Though the present results are surprising, they provide some insight into the published results from recent randomised clinical trials in postmenopausal women that have shown that oestrogen alone increased the risk of second stroke (Viscoli et al, 2001) and that conjugated equine oestrogen plus medroxyprogesterone increased overall health risks including an increase in stroke rate (Rossouw et al, 2002). Thus, oestrogen clearly has the potential to both ameliorate or exacerbate brain injury and the overall effect of the hormone is possibly determined by a complex interplay of opposing mechanisms that will be influenced by the completeness and duration of blood vessel occlusion, the nature of the brain injury, and the duration and dose of oestrogen treatment.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Though the present results are surprising, they provide some insight into the published results from recent randomised clinical trials in postmenopausal women that have shown that oestrogen alone increased the risk of second stroke (Viscoli et al, 2001) and that conjugated equine oestrogen plus medroxyprogesterone increased overall health risks including an increase in stroke rate (Rossouw et al, 2002). Thus, oestrogen clearly has the potential to both ameliorate or exacerbate brain injury and the overall effect of the hormone is possibly determined by a complex interplay of opposing mechanisms that will be influenced by the completeness and duration of blood vessel occlusion, the nature of the brain injury, and the duration and dose of oestrogen treatment.…”
Section: Discussionmentioning
confidence: 54%
“…However, other studies have reported the opposite effect. The Framingham Heart Study (Wilson et al, 1985), an observational study, found that postmenopausal women on ERT had an increased risk of stroke, while a placebo-controlled randomised trial found that oestradiol did not reduce stroke mortality rates and, in fact, increased the risk of fatal stroke (Viscoli et al, 2001). A further observational study suggested that low-dose oestrogen treatment decreased the risk of coronary events and stroke, but that a higher dose may increase the risk of stroke (Grodstein et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The combined therapy seems to attenuate a detrimental effect of HRT on plaque stability. Many other studies have reported similar short-term harmful effects after initiating HRT in high-risk patients [3,6,26,27]. When HRT is started shortly after an acute MI, a significantly 44% higher risk of unstable angina pectoris, death and re-infarction is seen compared to chronic users and never users [28].…”
Section: Initiating Hrt In Chd Patientsmentioning
confidence: 67%
“…All randomised trials of HRT-use in women with an increased risk of CHD have failed to show any benefit on the vascular system [1][2][3]. Recent data from two more randomised angiographic studies, the WAVE-trial and the WELL-HART study, confirm the lack of benefit of HRT on the progression of coronary atherosclerotic lesions in women with documented coronary heart disease [23,24].…”
Section: Initiating Hrt In Chd Patientsmentioning
confidence: 99%
See 1 more Smart Citation